Asynchronous communication in Java over Infiniband and DECK - Righi, Rd. R.; Navaux, P. O. A.; Cera, M. C.; Pasin, M. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2005)
Java is becoming an attractive and easy to use programming language. It provides two systems for distributed computing, RMI and sockets, which describe a synchronous communication over TCP/IP. These Java core features may not be the best choice for cluster computing environments, since they do not provide high performance, a critical factor in this scenario. In this paper, presented is the development of Aldeia system, a library proposal to provide asynchronous communication in Java for cluster programming. Aldeia has been deployed on SAN hardware through Infiniband and DECK high-speed substrates. This paper shows the rationale for Aldeia's creation, its structure and encouraging results in synchronous and asynchronous approaches.